2019
DOI: 10.3390/agronomy9110705
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Organic Substrates and Microorganisms as Bio-Fertilisation Tool in Container Crop Production

Abstract: Microorganisms are only effective when adequate conditions for their survival and development are provided. Among the factors that influence its effectiveness includes the type of soil or culture substrate, which works as an energy source reserve. Therefore, a tomato and a melon crop were established in different cycles to assess the effect of the physicochemical properties of organic substrates based on coconut fibre and vermicompost in three proportions, 0:100, 40:60 and 60:40 (% v:v), on the microbial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Except for lycopene, the higher presence of antioxidant compounds found in tomatoes treated with the highest dose of vermicompost (V9), with respect to the tomatoes treated with a 3 kg m −1 dose (V3), may be explained by the higher presence of microorganisms and an improvement in enzymatic activity when a higher dose of vermicompost is applied [56]. However, the differences in microbial activity are not completely related to the concentration of macronutrients in soil recorded in this study, and biological activity should be analysed [56] to understand the differences in results. PO 4 2− , N Kjeldahl, Mg 2+ and O.M.…”
Section: Influence Of Soil Proprieties On Tomato Yield and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Except for lycopene, the higher presence of antioxidant compounds found in tomatoes treated with the highest dose of vermicompost (V9), with respect to the tomatoes treated with a 3 kg m −1 dose (V3), may be explained by the higher presence of microorganisms and an improvement in enzymatic activity when a higher dose of vermicompost is applied [56]. However, the differences in microbial activity are not completely related to the concentration of macronutrients in soil recorded in this study, and biological activity should be analysed [56] to understand the differences in results. PO 4 2− , N Kjeldahl, Mg 2+ and O.M.…”
Section: Influence Of Soil Proprieties On Tomato Yield and Qualitymentioning
confidence: 99%
“…Furthermore, vermicompost has the largest fraction of degraded organic matter compared with the other organic amendments, resulting in higher nutrient availability. The application of vermicompost can also enhance microbial activity in the soil, thus improving the N availability for plants [55,56]. However, a study by Mejia et al [28] in a soilless experiment demonstrated that higher doses of vermicompost lead to higher microbial activity, but the N concentration in the substrate does not increase.…”
Section: Influence Of Soil Proprieties On Tomato Yield and Qualitymentioning
confidence: 99%
“…The presence of cornmeal served Coniothyrium as a source of carbohydrates for optimal growth without affecting the development of the plant. In another study, substrates with high levels of organic matter as vermicompost or coconut fiber showed greater enzymatic activity of plant growth‐promoting bacteria present in them, such as Frateuria aurantia , among others (Ruiz et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The promoter effect of beneficial microorganism must be to an integral part of the biological cycle of nutrients, facilitating their availability for plants. It is necessary to characterize substrates to determine their ability to influence microbial activity which is a fundamental factor in maintaining sustainability and productivity (Fu et al., 2017; Ruiz, del, & Salas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[38]. Frateuria aurantia is another important KSB [131]. KSB dissolve silicate and release Kand these can be effective bioinoculants for the future.…”
Section: Nutrient Assimilation and Biofortificationmentioning
confidence: 99%